Peculiarities of the instrumental competitions functioning in the context of performing arts development (Journal of Namibian Studies : History Politics Culture, 2023)
The research aimed to determine the distinctive features of contemporary performing arts and their reflection in the specifics of the instrumental competitions. In particular, the roles of the jury and the audience are considered in the context of the influence on the development of the musical career and skill of participants in the competitions and the vectors of instrumental music development in general. Particular attention in the study is paid to musical works created using the latest digital technologies. In general, the role of instrumental competitions in shaping the development vectors of the performing arts and accompanying concerns are outlined.